FAKTOR-FAKTOR PENYEBAB TINGGINYA TINGKAT GUGAT CERAI DI KECAMATAN PAYUNG SEKAKIKOTA PEKANBARU - ", Halimah; Kadarisman, Yoskar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The research was done in the district town pekanbaru a foot umbrella. in order to determine factors causing the high rate of divorce in pekanbaru. Problems in this study were (1) Anyone who does divorce in the district town pekanbaru a foot umbrella (2) what are the factors causing the high rate of divorce.This research is quantitative descriptive, however, to complement and strengthen the data analysis researchers also conducted a qualitative analysis of the respondents, so the analysis will be undertaken more perfect. population in this study were widows who exist in the district town pekanbaru a foot umbrella which amounted to 165 people. Then the sampling technique used was simple random sampling (simple random) that 36 people out of a population of 165 people. To collect the data the researchers used in-depth interviews with respondents, literature study, and documentation. Based on the research results can be concluded that the factors causing the high rate of divorce in the district town city pekanbaru a foot umbrella is (1) domestic violence as many as 16 cases (44.44%), (2) infidelity as much as 9 cases (25%), ( 3) the economy as much as 7 cases (14.44%), and (4) the intervention of a third party (parents) as much as 4 cases (11.12%).Key word : the factor divorce, confuse claim, and religious courts 1 Pekanbaru.